Step
*
1
of Lemma
quadratic-formula2
1. a : ℝ
2. b : ℝ
3. c : ℝ
4. a ≠ r0
5. r0 ≤ ((b * b) - r(4) * a * c)
6. r(2) * a ≠ r0
7. v : {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
8. rsqrt((b * b) - r(4) * a * c) = v ∈ {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
9. r0 ≤ v
10. (v * v) = ((b * b) - r(4) * a * c)
11. x : ℝ
12. ((a * x^2) + (b * x) + c) = r0
⊢ (¬¬((x = (-(b) + v/r(2) * a)) ∨ (x = (-(b) - v/r(2) * a))))
∧ ((((r(2) * a) * x) + b ≠ r0 ∨ (r0 < ((b * b) - r(4) * a * c)))
  
⇒ ((x = (-(b) + v/r(2) * a)) ∨ (x = (-(b) - v/r(2) * a))))
BY
{ Assert ⌜((r(2) * a) * x) + b^2 = ((b * b) - r(4) * a * c)⌝⋅ }
1
.....assertion..... 
1. a : ℝ
2. b : ℝ
3. c : ℝ
4. a ≠ r0
5. r0 ≤ ((b * b) - r(4) * a * c)
6. r(2) * a ≠ r0
7. v : {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
8. rsqrt((b * b) - r(4) * a * c) = v ∈ {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
9. r0 ≤ v
10. (v * v) = ((b * b) - r(4) * a * c)
11. x : ℝ
12. ((a * x^2) + (b * x) + c) = r0
⊢ ((r(2) * a) * x) + b^2 = ((b * b) - r(4) * a * c)
2
1. a : ℝ
2. b : ℝ
3. c : ℝ
4. a ≠ r0
5. r0 ≤ ((b * b) - r(4) * a * c)
6. r(2) * a ≠ r0
7. v : {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
8. rsqrt((b * b) - r(4) * a * c) = v ∈ {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
9. r0 ≤ v
10. (v * v) = ((b * b) - r(4) * a * c)
11. x : ℝ
12. ((a * x^2) + (b * x) + c) = r0
13. ((r(2) * a) * x) + b^2 = ((b * b) - r(4) * a * c)
⊢ (¬¬((x = (-(b) + v/r(2) * a)) ∨ (x = (-(b) - v/r(2) * a))))
∧ ((((r(2) * a) * x) + b ≠ r0 ∨ (r0 < ((b * b) - r(4) * a * c)))
  
⇒ ((x = (-(b) + v/r(2) * a)) ∨ (x = (-(b) - v/r(2) * a))))
Latex:
Latex:
1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  c  :  \mBbbR{}
4.  a  \mneq{}  r0
5.  r0  \mleq{}  ((b  *  b)  -  r(4)  *  a  *  c)
6.  r(2)  *  a  \mneq{}  r0
7.  v  :  \{r:\mBbbR{}|  (r0  \mleq{}  r)  \mwedge{}  ((r  *  r)  =  ((b  *  b)  -  r(4)  *  a  *  c))\} 
8.  rsqrt((b  *  b)  -  r(4)  *  a  *  c)  =  v
9.  r0  \mleq{}  v
10.  (v  *  v)  =  ((b  *  b)  -  r(4)  *  a  *  c)
11.  x  :  \mBbbR{}
12.  ((a  *  x\^{}2)  +  (b  *  x)  +  c)  =  r0
\mvdash{}  (\mneg{}\mneg{}((x  =  (-(b)  +  v/r(2)  *  a))  \mvee{}  (x  =  (-(b)  -  v/r(2)  *  a))))
\mwedge{}  ((((r(2)  *  a)  *  x)  +  b  \mneq{}  r0  \mvee{}  (r0  <  ((b  *  b)  -  r(4)  *  a  *  c)))
    {}\mRightarrow{}  ((x  =  (-(b)  +  v/r(2)  *  a))  \mvee{}  (x  =  (-(b)  -  v/r(2)  *  a))))
By
Latex:
Assert  \mkleeneopen{}((r(2)  *  a)  *  x)  +  b\^{}2  =  ((b  *  b)  -  r(4)  *  a  *  c)\mkleeneclose{}\mcdot{}
Home
Index